Deliberative democracy - O'Flynn, Ian (Polity Press, 2022)
Today, deliberative democracy is the most widely discussed theory of democracy. Its proponents argue that important decisions of law and policy should ideally turn not on the force of numbers but on the force of the better argument. However, it continues to strike some as little more than wishful thinking.